Makoiamya cotterallae, a new genus and species of bivalve (Ceratomyidae) from the latest Triassic of New Zealand and New Caledonia - Grant-Mackie, John A. (Zootaxa, 2013)
The new genus and species Makoiamya cotterallae is erected for fossil bivalves previously informally identified as Anodontophora Alberti (= Unionites Wissmann) or a relative or Ochotomya Polubotko in the Late Triassic Murihiku Terrane of New Zealand and Téremba Terrane of New Caledonia (Norian and Rhaetian; Warepan and Otapirian local stages). Neither of these genera happily accommodates these shells and a new genus is considered necessary for them. Makoiamya fits most readily into the Ceratomyidae and members were burrowers in fine sand and silt, where they are generally preserved in life orientation.